Word and world - Gaiser, Frederick J. (Word & world, 2016)
With the practiced eye of someone who has wrestled with the theme of Word and World for many years as editor of this journal (1987–2016), Fred Gaiser reflects on the ways in which these two poles have defined and shaped theological reflection over the thirty-five-year history of our journal, and how these twin foci are still vitally important for the Christian community.